Large Left Ventricular Thrombus in a Patient with Systemic and Venous Thromboembolism Secondary to Protein C and S Deficiency - Mohit Pahuja; Bujji Ainapurapu; Aiden Abidov (Case Reports in Cardiology)
58-year-old Hispanic female presented with an altered mental status. A CT scan of the head demonstrated multiple scattered infarcts and a large right temporal lobe infarct. We also diagnosed the patient with right popliteal and femoral vein thrombosis, bilateral pulmonary embolism, and a transient right radial artery occlusion. Her 12-lead EKG showed lateral ST elevation. Emergent coronary angiogram revealed normal coronaries. Echocardiogram demonstrated a large mobile mass attached to the anterolateral free wall with overall normal contractility of the left ventricle. The patient underwent surgical embolectomy to prevent further systemic embolization. Coagulability workup returned positive for protein C and S deficiency. The patient did well after surgery. Following her surgery, we initiated chronic oral anticoagulation. The presentation with intracardiac thrombus in a normal heart should raise a concern of a probable thrombophilia.